The Improvisation in Arts: - Issa, Yahya; Al-Abbas, Mohammed; Jawabra, Nser (Dirasat: Human and Social Sciences, 2020)
This study aims to identify the elements and mechanisms of improvisation in Arts. Therefore, it investigates the methodologies of improvisation in the theater of the oppressed which is a theatrical approach established by Augusto Boal. Thus, different arts used improvisation techniques as a form of expression. It appeared in the musical arts, performance arts, visual arts, as well as theater arts. The limitations of this study located number of artistic projects made in the 20th century. The researchers used the analytical descriptive approach in this study, which is significant because it highlights the subject of improvisation in the arts in general, and in theater in particular. This study serves the art students, as well as provides awareness to academic institutions such as colleges of fine arts.